CRITO-MYCENEAN ERA AND GREEK MYTHOLOGY - Mamadkulova Kamila Abdukhalikovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article is devoted to the Cretan-Mycenaean era and Greek mythology. About the literary adaptation of the ancient fairy tale “Cupid and Psyche” in the novel by a Roman writer of the 2nd century. n. e. Apuleius "Metamorphoses"